Oral Dental Health and Hygiene Maintenance for Pregnant Women at Taram Public Health Center in Lima Puluh Kota Regency - Minarni Minarni; Zulfikri Zulfikri; Muhammad Faisal; Arnetty Arnetty (Lembaga Pengembangan Kinerja Dosen, 2022)
Oral Health and Hygiene Maintenance for Pregnant Women at Taram Public Health Center in Lima Puluh Kota Regency. Hormonal changes in pregnant women cause various complaints, such as cravings, nausea, vomiting, including toothache as a result of neglecting oral hygiene. Changes in diet and habits of not maintaining oral hygiene due to fatigue, nausea and vomiting in some pregnant women can increase the risk of dental and oral diseases, which will affect the condition of their pregnancy. This type of research is descriptive with a sample size of 124 people taken by simple random sampling. The research was conducted at Taram Public Health Center in Lima Puluh Kota Regency. The data was collected by distributing questionnaires to determine the actions of pregnant women in maintaining oral hygiene, as well as conducting dental and oral hygiene checks based on the Oral Hygiene Index (OHIS-S). The results showed that oral health and hygiene maintenance for pregnant women in the work area of the Taram Public Health Center was good, but the oral hygiene are moderate. Based on research on 124 pregnant women in the working area of the Taram Public Health Center, it can be concluded that the oral dental and hygiene maintenance actions of pregnant women are mostly in the good category.